Handbook of environmental degradation of materials - Kutz, Myer (William Andrew Pub., 2005)
Industry pays an enormous price for material degradation. The Handbook of Environmental Degradation of Materials outlines these costs, but more importantly, explains how to measure, analyze, and prevent environmental degradation for a wide range of industrial materials. Experts from around the world share how a diverse set of industries cope with the degradation of metals, polymers, reinforced concrete, clothing, and wood under adverse environmental conditions such as weather, seawater, and fire. Case studies show how organizations from small consulting firms to corporate giants design and manufacture products that are more resistant to environmental effects. By implementing these standards companies of all sizes should realize savings beneficial to their operations.